Hubungan Pusat-Daerah Gelombang Ketiga: sosok Otonomi Daerah di Indonesia Pasca Soeharto - - Pratikno (Unisia, 1999)
Undoubtedly, the New Era regime has made an excellent reputation in facing rebellions by local governments [provincies] inherited by the Old Regime. However, the repression and otoritarianism acted by the New Era has caused another danger, that is, the 'revenge' of the provinces against the central government. There are three points that must be considered to be enforced in the next area; First, the national political system must represent the local representative elected in fair way. Second, democratization among local governments must be strongly introduced to avoid otoritarianism in the local governments. Third, between the local supra-structure and the national supra-structure must be clearey separated. Fourth, another mechanism other than the representation through the House of Representative is urgently needed as a gateway for local governments to take part in setting up the national policies.